Traversing the Center: The Politics of Language Use in a Catholic Religious Education Program for Immigrant Mexican Children - Baquedano-López, Patricia (Anthropology & education quarterly, 2004)
This article examines the implementation of educational policy in a religious education program at a Los Angeles Catholic parish. It charts the elimination of Spanish-based classes (doctrina) for Mexican immigrant children in favor of "English-only" instruction. The article offers insights into the politics of language use in everyday practice and examines the resulting educational policy decisions.